Filsafat Bahasa dalam Kajian Linguistik : Analisis Konseptual tentang Makna dan Penggunaan Bahasa - Erli Sarina; A. Muh. Taufiq (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the contribution of philosophy of language in linguistic studies, particularly related to the concept of meaning and language use. The main problem studied is how philosophy of language provides a conceptual foundation for understanding the meaning of language that is not only structural, but also contextual and pragmatic. This study uses a qualitative method with a library research approach through conceptual analysis of the works of philosophers of language and contemporary linguistic literature. The results of the study indicate that philosophy of language plays an important role in expanding linguistic perspectives, especially in understanding meaning as a result of language use in social practice. Concepts such as context, speaker intention, and rules of language use are central aspects in bridging the philosophy of language and linguistics. This finding confirms that the study of meaning cannot be separated from the philosophical dimensions that underlie it. The conclusion of this study is that the integration of philosophy of language in linguistic studies provides a more comprehensive theoretical framework in understanding the meaning and use of language, making it relevant for the development of language and communication studies in the contemporary era.